PENGUKURAN KINERJA KEUANGAN PEMERINTAH DAERAH KOTA KENDARI 2015-2021 - Muslim, Caesar; Saenong, Zainuddin; Hastuti, Hastuti (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2023)
Measuring local government financial performance is very important because it provides a basis for evaluation, effective management and accountability in the management of public financial resources. This research aims: (1) To determine the Regional Tax Effectiveness Ratio for Kendari City; (2) To find out the Kendari City Regional Financial Independence Ratio; (3) To find out the Ratio of Regional Tax Contribution to Kendari City PAD. The results of this research show that: (1) The Financial Performance of the Kendari City Regional Government in realizing the target PAD base that was previously determined using the Effectiveness Ratio is classified as Still Not Effective. (2) Regional financial independence ratio during 2015-2021 which produces an average of 20.87% (capacity is still very low) with an instructive relationship pattern. This means that the dependence of the Kendari City government is still very high regarding sources of aid funds from external parties, both from the central government and from the provincial government. (3) The contribution of Regional Tax to Kendari City's PAD, averaged from 2015-2021, is 47.09% or falls under the Adequate criteria.